Efektivitas Tayangan Film Umar bin Khattab di MNC TV terhadap Tingkat Pemahaman Keislaman Mahasiswa - Hermansyah Hermansyah; Komariah Komariah (STID DI AL-HIKMAH, 2015)
The research objective was to determine whether the airing of historical drama Umar through television media is effective in improving the understanding of Islam among the students of the Faculty of Mathematics and Natural UNJ . In this research method used is descriptive quantitative research using survey method with cross sectional approach . The conclusion is the interpretation of research results between impressions Umar bin Khatttab to the level of understanding of Islamic Students of the Faculty of Science at the State University of Jakarta could otherwise have a strong enough relationship.